The current capacity and quality of colonoscopy in Korea - Jae Ho Choi (Intestinal Research, 2019)
Background/Aims Little is known for the capacity and quality of colonoscopy, and adherence to colonoscopy surveillance guidelines in Korea. This study aimed to investigate the present and potential colonoscopic capacity, colonoscopic quality, and adherence to colonoscopy surveillance guidelines in Korea. Methods We surveyed representative endoscopists of 72 endoscopy units from June to August 2015, using a 36-item questionnaire regarding colonoscopic capacity, quality, and adherence to colonoscopy surveillance guidelines of each hospitals. Results Among the 62 respondents who answered the questionnaire, 51 respondents were analyzed after exclusion of 11 incomplete answers. Only 1 of 3 of endoscopy units can afford to perform additional colonoscopies in addition to current practice, and the potential maximum number of colonoscopies per week was only 42. The quality of colonoscopy was variable as reporting of quality indicators of colonoscopy were considerably variable (29.4%–94.1%) between endoscopy units. Furthermore, there are substantial gaps in the adherence to colonoscopy surveillance guidelines, as concordance rate for guideline recommendation was less than 50% in most scenarios. Conclusions The potential capacity and quality of colonoscopy in Korea was suboptimal. Considering suboptimal reporting of colonoscopic quality indicators and low adherence rate for colonoscopy surveillance guidelines, quality improvement of colonoscopy should be underlined in Korea.